HKDC1 promotes ovarian cancer progression through boosting lipid metabolism and immune escape by stabilizing G6PC/G6PC2 - Ying Wang; Juan Chen; Zhan Wang; Xia Luo; Nayiyuan Wu; Jing Wang (Communications Biology)
Abstract Ovarian cancer (OC) is a significant health challenge, yet the mechanisms driving its progression remain unclear. This study explored the role of hexokinase domain-containing protein 1 (HKDC1) in OC, focusing on tumor growth, lipid metabolism, and immune evasion. Human OC cell lines (SKOV3 and HEY) and the murine OC cell line (ID8) were used to knock down and overexpress HKDC1. An ID8-based epithelial OC mouse model was established to validate the in vitro findings. Our results demonstrated that HKDC1 was upregulated in OC and promoted cell proliferation, migration, and invasion. HKDC1 enhanced lipid accumulation by elevating levels of free fatty acids (FFA), triglycerides, phospholipids, cholesterol, and neutral lipid, while upregulating key enzymes (ACC1, FASN, SCD1, HMGCS1, and HMGCR). It promoted immune escape through PD-L1 upregulation, inhibiting T cell proliferation and reducing IFN-γ, granzyme B, and perforin levels while increasing PD-1 levels. HKDC1 knockdown reversed these effects, which were restored by adding FFA. Mechanistically, HKDC1 interacted with and stabilized glucose-6-phosphatase catalytic subunits (G6PC/G6PC2), supporting its tumor-promoting functions. These findings were confirmed in an OC mouse model, highlighting HKDC1 as a key driver of OC progression through lipid biosynthesis and immune suppression, offering potential therapeutic targets.